Promoção de saúde mental para jovens pré-vestibulandos, utilizando ciclo de intervenções psicoeducacionais - Freitas, Stephane de Paiva (Universidade Federal de São Carlos, 2020)
The study aimed to discuss the influences of psychoeducational interventions on the prevalence of common mental disorders aiming the promotion of mental health in pre-university students. The research scenario was a non-profit course focused on university entrance exam in the city of São Carlos (SP). Two 18-year-old female students participated. Data collection was done based on the response to the Self Report Questionnaire 20 (SRQ-20), focal group and semi-structured interviews. Analysis were made using the theoretical frameworks of Public Health and Content Analysis. The results indicated the inseparability of the cultural, social, financial, educational deficit and development dimensions as triggers and / or maintainers of psychological suffering in this phase. Both cited the intervention as one of the mechanisms that promote teaching and mental health when added to specific pre- university classes, religion and psychotherapy. It was concluded, therefore, the importance of intersectoral actions and universal access to higher education for this public, as well as a greater number of participants in future studies.
Promotion of mental health for pre-vestibulate young people, using a cycle of psychoeducational interventions
Keywords: Saúde mental; Saúde coletiva; Sofrimento psíquico; Jovens pré vestibulandos; CIENCIAS HUMANAS::PSICOLOGIA